The MBA startup clinic: An experiential team-teaching approach for entrepreneurial leadership - Sánchez Coll, Felipe; Donaldson, Colin; Villagrasa, Jorge (Journal of Management and Business Education, 2025)
This paper presents the teaching methodology applied in the “Global Context” course within the Junior MBA program at EDEM University. This intensive three-day course, delivered in English as part of the “Innovation and Strategy” module, comprises five hours of instruction per day. It aims to develop entrepreneurial leadership skills by encouraging students to shift from conventional, linear problem-solving to more agile and adaptive framework. A critical shift for future leaders in today’s volatile and uncertain global business environment. The course applies active learning techniques, including interactive lectures, open discussions, start-up case analysis, and team-based assessments, with primary emphasis on a collaborative team-teaching model. This approach is integrated with the MBA Startup Clinic, a hands-on project designed to bridge theoretical foundations with practical application. Course effectiveness was evaluated through structured surveys that gathered qualitative feedback from students. Results indicate a significant improvement in students’ ability to tackle complex challenges. Notably, 82% reported feeling better prepared for real-world business environments. However, a minority, 18%, expressed some discomfort with the interactive dynamics of team-teaching, particularly when instructors engaged in spontaneous dialogue that occasionally diverged from their expectations of a more conventional lecture structure.